2006
DOI: 10.1103/physrevlett.96.186403
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Electronic Correlations in the Ground State Momentum Density ofAl97Li3

Abstract: We report high resolution Compton scattering measurements on an Al(97)Li(3) disordered alloy single crystal for momentum transfer along the [100], [110], and [111] symmetry directions. The results are interpreted via corresponding Korringa-Kohn-Rostoker coherent potential approximation first-principles computations. By comparing spectra for Al(97)Li(3) and Al, we show that the momentum density in the alloy differs significantly from the predictions of the conventional Fermi-liquid picture and that the ground s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Here valence Compton profiles can be used for background subtraction. In addition, our method could explain some anomalies observed in Al 97 Li 3 alloys [59].…”
Section: Discussionmentioning
confidence: 76%
“…Here valence Compton profiles can be used for background subtraction. In addition, our method could explain some anomalies observed in Al 97 Li 3 alloys [59].…”
Section: Discussionmentioning
confidence: 76%
“…In fact, x-ray Compton scattering has been used as a robust technique for investigating wave-function characters [2,28,29] and Fermi surfaces [30][31][32] in wide classes of materials. Compton scattering has also been applied to study charge transfers in metal alloys [33][34][35][36] and also in Li battery cathode materials [37]. Moreover, the determination of the Mulliken analysis has been very successful to explain the behavior of the Compton profile in Si clathrates [38].…”
mentioning
confidence: 99%
“…For studies of magnetic materials, information on spin states of electrons is important. During the years since 1976 [1], it has been found that magnetic Compton scattering of circularly polarized X-rays is effective for measuring MD distribution of electron spins in ferro/ferri-magnetic materials, such as metals, alloys and compounds, all of which are composed of 3d-transition and/or 4f-rare-earth elements [2]. Following an introduction to characteristic features of magnetic Compton scattering, recent progress will be briefly reviewed by referring to notable reports.…”
Section: Momentum Density Of Uncompensated Electron Spins Measured Bymentioning
confidence: 99%